GALLIUM OXIDE CATALYST SUPPORTED ON CERIA-ZIRCONIA COMPOSITE SUPPORT, PREPARATION METHOD THEREOF AND PRODUCTION METHOD FOR DIMETHYL CARBONATE USING SAID CATALYST - SONG, IN KYU; PARK, DONG RYUL; LEE, HYE JIN (2012)
PURPOSE: Ceria-zirconia complex carrier carried gallium oxide catalyst for manufacturing dimethyl carbonate, a method for manufacturing the same, and a method for manufacturing the dimethyl carbonate using the catalyst are provided to improve the reactivity of the catalyst and to improve the yield of the dimethyl carbonate. CONSTITUTION: Ceria-zirconia complex carrier carried gallium oxide catalyst for manufacturing dimethyl carbonate is used for manufacturing dimethyl carbonate based on methanol and carbon dioxide. In the gallium oxide catalyst, the molar ratio of ceria and zirconia is 0 to infinity. The complex of the ceria-zirconia is represented by Ce_xZr_1-xO_2. In chemical formula, x is 0 to 1. The complex of the ceria-zirconia is manufactured based on a sol-gel method. A method for manufacturing the catalyst includes the following: two kinds of precursor aqueous solutions based on a cerium precursor and a zirconium precursor are prepared; citric acid aqueous solution is prepared by dissolving citric acid in distilled water; the citric acid aqueous solution is applied to the precursor aqueous solution to obtain sol; the sol is gelated; the gel is dried and plasticized to obtain ceria-zirconia carrier; gallium oxide is immersed in the carrier and dried and plasticized.